In situ expression of Th17 immunologic mediators in American cutaneous leishmaniasis caused by Leishmania (V.) braziliensis and Leishmania (L.) amazonensis in the Brazilian Amazon - Rodrigues, Gabriela F.; Alcântara, Larissa Santos; Barros, Joyce Pietro B.; de Lima, Ana Carolina S.; Campos, Marliane B.; Moraes, Cesar; Ferreira, Aurea F.; Matta, Vania Lucia R.; Laurenti, Marcia D.; Corbett, Carlos Eduardo P.; Silveira, Fernando T.; Gomes, Claudia Maria Castro (Frontiers in Tropical Diseases, 2023)
American cutaneous leishmaniasis (ACL) presents a wide spectrum of clinical and immunopathological manifestations. In Brazil, Leishmania (L.) amazonensis[La] and Leishmania(V.)braziliensis[Lb] show the highest pathogenic potential for humans causing different clinical forms: localized cutaneous leishmaniasis (LCL : Lb/La), anergic diffuse cutaneous leishmaniasis (ADCL : La) and mucocutaneous leishmaniasis (MCL : Lb). ADCL and MCL are the most severe forms and infection leads to a cellular immune response at the hyposensitivity and hypersensitivity poles. Th17-cells are involved in the ACL pathogenesis, are derived from naïve TCD4+ cells regulated by RORγt, differentiate in presence of IL-6, TGF-β, IL- 1β, IL-23 and express IL-17. Aim of this study was to characterize the cellular immune response mediated by Th17-profile cells through in situ determination of the expression of RORγt, IL-17, IL-6, TGF-β, IL-1β, and IL-23 in the ACL clinical-immunopathological spectrum caused by L.(L.)amazonensis and L.(V.)braziliensis. Biopsies of skin and mucosal lesions from forty patients including ADCL(n=8), LCL[La](n=17), LCL[Lb](n=9) and MCL(n=6), were examined by immunohistochemistry. The immunostained cells density (cells/mm2) was determined in image analysis system using AxionVision 4.8 software (Zeiss). As the disease evolution time (DET) was different among ACL patients, the effect of DET on the expression of immunological markers was evaluated in different clinical forms and histopathological changes, using ANCOVA. Our results showed significantly increased expression of RORγt, IL-17, IL-6, IL-1β and IL-23 in patients with ACL polar forms (ADCL and MCL); higher TGF-β expression was found in ADCL. DET influenced the expression of RORγt and IL-6 in: clinical forms of ACL and in categories of parasitism. DET also affected the production of RORγt, IL-17, IL-6, TGF-β and IL-1β in types of inflammatory infiltrate, evidencing that DET had effect on the expression of Th17 profile cytokines in ACL. Together, the expression of immunological mediators of Th17 profile in the ACL spectrum, as well as the DET effect, demonstrate the participation of this cell lineage in the immunopathogenesis of ACL, mainly in the polar and more severe forms of ACL spectrum. The dubious role played by Th17-cells may favors immune response suppression and parasitic persistence in ADCL, while in MCL it contributes to an exacerbated immune response and parasite scarcity.